Pioneer study of SiP2 as negative electrode for Li- and Na-ion batteries. Issue 9 (12th February 2016) - Duveau, D.; Israel, S. Sananes; Fullenwarth, J.; Cunin, F.; Monconduit, L.
Abstract : For the first time it is demonstrated that a dense SiP2 pyrite-type obtained by a very simple ball milling method delivers outstanding capacity in both lithium and sodium batteries with up to 1000 mA h g −1 and 572 mA h g −1 sustained after 30 and 15 cycles respectively. Abstract : For the first time it is demonstrated that a dense SiP2 pyrite-type obtained by a very simple ball milling method delivers outstanding capacity in both lithium and sodium batteries with up to 1000 mA h g −1 and 572 mA h g −1 sustained after 30 and 15 cycles respectively.